Does the presentation of neonatal abstinence syndrome symptoms differ among infants based on exposure substance? - Desaulniers, Lindsay (My University, 2014)
INTRODUCTION: Neonatal abstinence syndrome (NAS) is one of the primary negative effects of substance use during pregnancy. Neonatal abstinence syndrome refers to a generalized disorder observed in infants experiencing opiate withdrawal. Signs and symptoms of NAS include yawning, sneezing, sweating, stuffy nose, mottling, fever and increased secretion of tears, and often the development of tremors, high pitched cry, increased muscle tone and irritability. The modified Finnegan scoring tool is widely used to assess NAS and guide NAS treatment. However, the emphasis is usually on the total score. Little is known about which symptoms (individual items) on the modified Finnegan Scoring Tool are the most commonly observed among infants presenting with NAS and whether they differ based on type of substance exposure. Similarly, little is known whether the severity of NAS differs based on the type of substance exposure. Thus, the purpose of this study was to evaluate whether the presentation of NAS symptoms, severity of NAS and neonatal outcomes differ among infants based on the substances they were exposed to in utero. METHODS: A retrospective chart review was conducted collecting data from infant and maternal health records (over a one year period) from a tertiary care hospital. ANALYSIS: Descriptive statistics, Chi-Square and One-way Analysis of Variance (ANOVA) using the Student- Newman-Keul (SNK) post hoc comparisons were conducted to determine whether significant differences existed between groups on outcome variables based on exposure substance. RESULTS: Data were collected on 131 infantjmother pairs. Infants were categorized by exposure substance into one of four groups; methadone only, methadone and other substances, single non-methadone, and poly non-methadone. Three symptoms (increased muscle tone, tremors when disturbed and fever between 37.2°C and 38.3°C) were identified as the most common symptoms observed across all four groups of infants. Two symptoms (generalized convulsions, fever :?38.4°C) were never observed in any of the four groups, and ten symptoms were seen at a frequency of less than 5% in any of the groups. No clear significant differences were found between the four groups on the relative frequency of symptom observation. However, infants exposed to methadone (solely or in addition to other substances) experienced more severe NAS compared to infants not exposed to methadone. This was demonstrated by the significantly higher peak scores, longer time from onset of symptoms to peak score, larger number of infants requiring pharmacological treatment, longer length of treatment and longer lengths of stay in hospital. No significant differences among the four groups were found for any of the neonatal outcomes including term, weight, length, head circumference, and one minute and five minute Apgar scores. CONCLUSION: Infants exposed to methadone (alone or with other substances) experienced more severe NAS after delivery than did those exposed to substances other than methadone. Further evaluation of and a possible reduction in the number of items on the modified Finnegan scoring tool is needed as many items were rarely if ever observed, regardless of the substance exposure. There are varying findings in the literature regarding differences in birth outcomes based on substance exposure, further investigation is justified.
Keywords: Substance exposure; Neonatal outcomes; Neonatal abstinence syndrome (NAS); Substance abuse during pregnancy